ChemInform Abstract: "Pruning of Biomolecules and Natural Products (PBNP)": An Innovative Paradigm in Drug Discovery. Issue 31 (August 2015) - Bathula, Surendar Reddy; Akondi, Srirama Murthy; Mainkar, Prathama S.; Chandrasekhar, Srivari
Abstract Review: [127 refs.